Development of proof-based student worksheets in trigonometry. (March 2020) - Ismerelda, I; Hartono, Y
Abstract: Research has been conducted for: (1) Developing student worksheets based on valid trigonometric mathematical proofs, (2) Developing student worksheets based on practical trigonometric mathematical proofs and (3) Knowing the advantages and limitations of validation student product based on trigonometric mathematical proof developed. The research method used is research and development (R&D) with a development model developed by Rowntree, using three stages, namely: (1) the planning stage, (2) the development phase and, (3) the evaluation phase. The results of data analysis can be concluded The results give meaning that the developed: (1) is appropriate and appropriate to use, because it is in accordance with core competencies, basic competencies, indicators, objectives, scenarios of teaching and learning activities and has phases that are measurable and clearly easily understood by students and can develop Student that have been developed to meet the eligibility as a good Student, (2) both at one to one stage and small groups based on the criteria of practical use for each indicator in the practicality category on good level. (3) Excellence Developed Students can increase motivation, foster interest in learning, foster an attitude of confidence, can foster an honest attitude, increase discipline and foster cooperation among fellow students.